Studies of the physical and chemical properties of 1,4 dioxane and their relevance to adsorption and transdermal absorption - Mahdi, Ali Jafar (Kansas State University, 2014)
1,4-Dioxane is a potentially carcinogenic solvent. It is a problematic groundwater contaminant because of its unique physical-chemical properties. It is found in a wide range of consumer products as a by-product contaminant. This research aimed to investigate contaminant properties and behavior of dioxane in the environment and also in the human body. The dioxane ability to decontamination by adsorption processes was evaluated with four adsorbents. The adsorption efficiencies of activated carbon (AC), metal oxide nanomaterials (TiO[subscript]2 and MgO), and diatomaceous earth (DE) were assessed in aqueous and vapor phases using infrared spectroscopy. AC showed the highest adsorptive capacity for dioxane at equilibrium in both phases. The rate and extent of dermal absorption are important in the analysis of risk from dermal exposure to dioxane. For this purpose, a new flow through diffusion system (FTDS) was developed by modifying a Bronaugh flow through diffusion cell with flow capacity in both the donor and receptor compartments and using attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR) as the analytical technique. FTDS can provide ‘real time’ quantitative high-density permeation data over time and is characterized by the simplicity of its use and the low cost of test samples. The in vitro dermal absorption study of dioxane across human skin showed that the absorption parameters of dioxane were 1.16 ± 0.22 hr, 5.7 X 10[superscript]-4 ± (0.62) cm/hr, 0.286 ± 0.035 mg/cm2/hr, 4.8 X 10-5 (± 0.32) cm[superscript]2/hr, and 1.99 ± 0.086 mg for lag time, permeability, steady-state flux, diffusivity, and total amount absorbed over 8 hr, respectively. The study of the effect of the surfactant sodium lauryl sulphate and solvent systems water, ethanol, propylene glycol, and ethyl acetate on permeation profiles revealed that these solvents and surfactants increased the permeation of dioxane significantly. The FT-IR spectra of stratum corneum treated with solvents showed that there was broadening of the CH[subscript]2 asymmetric stretching vibration of the CH[subscript]2 peak near 2920 cm[superscript]-1 only in samples treated with ethanol. The lipid extract precipitates were detected and were mostly composed of the stratum corneum lipid part.
Keywords: 1,4 Dioxane; Adsorption; Dermal absorption; Human skin; Water; Toxicology (0383)